Application of the Neuroform Atlas Stent in Intracranial Aneurysms: Current Status - Hou, Kun; Yu, Jinlu (Frontiers in Neurology, 2022)
The Neuroform Atlas stent (NAS) is the successor of the Neuroform EZ stent. The NAS is compatible with a low-profile 0.0165-inch microcatheter and is soft enough to pass through small and highly tortuous vessels. The NAS can be used in treating intracranial aneurysms at almost all locations, and its use is becoming increasingly common. However, there has not yet been a complete review of NAS applications. Therefore, we performed this review, which addresses several aspects of the NAS, mainly including its characteristics, clinical trials of its application in treating aneurysms, deployment techniques for the device, the prognosis and complications of its application in treating aneurysms, and antiplatelet requirements associated with its use. Based on the evidence reviewed here, as well as our experience, we found that the NAS is a promising device for treating intracranial aneurysms, especially complex and distal aneurysms. This stent can also be used as a powerful tool to assist in rescuing coil migration, completing dual-stent reconstruction, and coiling aneurysms via a transcirculation approach. The device may require antiplatelet therapy at a lower dose and over a shorter period than other stents. The deployment of the NAS to assist in aneurysm coiling can yield good clinical outcomes and an acceptable rate of complications. Thus, the NAS is a promising device.